Biopolítica e educação: desafios da inclusão escolar das pessoas com deficiência no neoliberalismo - Matos, Maria Angélica Pereira [UNESP] (2019)
The present research aims to bring a reflection, by the means of the Philosophy of Education, about the challenges of including the person with disabilities in the context of neoliberal biopolitics. It is a study based on the genealogical method, used by the French philosopher Michel Foucault, in which, when concerned with the formation of the subject in the present, questions the prevailing discourse of truth and its relationship with the production of knowledge-power. Through Foucauldian studies, we tried to understand how inclusion started to exist in modernity, passing through classical liberalism, which understood deficiencies as a social risk, basing its biopolitical strategy on disciplinary devices, by isolation in institutions such as the church, prison, etc. Subsequently, with neoliberalism, the strategies of security devices emerged, consisting in maximally capturing deviations, in order to normalize the management of life to the point that this life plays a role in the labor market. Thus, it was necessary to understand who these current inclusion subjects are, highlighting their difference as a people who refuse to be part of the population, due to accidental issues present in the condition of having a disability. In this sense, we tried to problematize the current inclusion policies, starting with the Salamanca Declaration and the most recent National Special Education Policy from the perspective of Inclusive Education. These policies, although they have a lot to contribute with a positive idea of power, by opening spaces for thinking about inclusion in the common school and by bringing people with disabilities together with other students considered “normal”, also bring other modes of exclusion underway. When perceived that in both policies, the specialized scientific bias anchors the main inclusion practices, it is possible to perceive the examining and deciphering role, placing the disabled person as an object-subject to be corrected, since the specialist's main function is to seek the specific deficiencies through the report, in order to understand the person only by what he presents in the disability, and no more than that. It implied thinking that the success of the current inclusion is in making the deficiency less apparent as possible by means of normalizing devices, which also nullify the part in which the deficiency expresses in the subject what is excluded from the normal and allow another dimension of thinking about oneself, and can make a difference that leads to other processes of subjectification. This policy weakens a biopolitics of life, because in times of reflux of State policies, market disputes intensify and place these subjects in unequal conditions, to the point of living on their own. Therefore, we try to think that this path proposed by Special Education still faces enormous challenges in the present, as it demands from the school actors a posture of welcoming these lives, as a way of making them, through their experience, their powers, able to produce a policy that fits their lives, as it is, at school and beyond. In other words, it is about producing an ethics that welcomes differences.